Cutaneous Squamous Cell Carcinoma with Invasion through Ear Cartilage. (16th May 2016) - Boisen, Julie; Malone, C. Helen; Kelly, Brent; Wagner, Richard F.
Abstract : Cutaneous squamous cell carcinoma of the ear represents a high-risk tumor location with an increased risk of metastasis and local tissue invasion. However, it is uncommon for these cancers to invade through nearby cartilage. Cartilage invasion is facilitated by matrix metalloproteases, specifically collagenase 3. We present the unusual case of a 76-year-old man with an auricular squamous cell carcinoma that exhibited full-thickness perforation of the scapha cartilage. Permanent sections through the eroded cartilage confirmed tumor invasion extending to the posterior ear skin.